Wastewater treatment practices in Africa - experiences from seven countries - Nikiema, Josiane; Figoli, A.; Weissenbacher, N.; Langergraber, G.; Marrot, B.; Moulin, P. (2013)
In this paper, existing wastewater treatment practices in 7 African countries, i.e. Algeria, Burkina Faso, Egypt, Ghana, Morocco, Senegal and Tunisia, are reported. Data were collected by questioning wastewater treatment plants managers as well as treated wastewater users in 2012. This study showed that 0.2 to 63 L/d/person of wastewater are treated in these countries, with the higher levels obtained for North Africa. Technically, treatment plants (mostly activated sludge and waste stabilization ponds) deal with high organic loads, uncontrolled input, power cuts and increasing wastewater flow rates. Poor operation and maintenance (O&M), in part caused by the lack of funds, high energy costs and lack of re-investments, is also a serious reported issue. Consequently, treatment plants often deliver insufficient effluent quality, which negatively affects the environment and acceptability of stakeholders towards the treated water. Other challenges, such as water availability, long-term impacts, financial and social constraints, affecting the reuse, are also discussed.